### Home > A2C > Chapter 6 > Lesson 6.2.5 > Problem 6-114

6-114.

Think of a linear function that has a *y*-intercept other than 0 and use it to check the relationship *f*(*a*) + *f*(*b*) = *f*(*a* + *b*).

For example, try the linear function *f*(*x*) = 2*x* + 3 (you should think of a different one for your own answer).

*f*(*a*) + *f*(*b*) = (2*a* + 3) + (2*b* + 3)*f*(*a* + *b*) = 2(*a* + *b*) + 3*f*(*a*) + *f*(*b*) = 2*a* + 2*b* + 6

But, 2*a* + 2*b* + 6 ≠ 2*a* + 2*b* + 3

*f*(*a*) + *f*(*b*) = *f*(*a* + *b*) is not true for all linear functions.